2017
DOI: 10.17531/ein.2017.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental studies on the rotating rotor with three active composite blades

Abstract: Numerical aNd experimeNtal studies oN the rotatiNg rotor with three active composite blades badaNia NumeryczNe i eksperymeNtalNe wirującego wirNika z trzema aktywNymi łopatami kompozytowymi [8], but the object of the research was a thin plate with PZT actuators.The aim of this paper is to determine the relation between the dynamics of a rotor blade with MFC elements in relative motion and the rotational movement of the hub. Constant angular velocity can generate undesired changes in the natural frequencies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…It can be observed that the natural frequency of the first bending mode increases with increasing the rotational speed. This phenomenon is known as the centrifugal stiffening effect [21]. Moreover, the second stiffening effect is observed, that is generated by the active element.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It can be observed that the natural frequency of the first bending mode increases with increasing the rotational speed. This phenomenon is known as the centrifugal stiffening effect [21]. Moreover, the second stiffening effect is observed, that is generated by the active element.…”
Section: Resultsmentioning
confidence: 97%
“…Generally, the value of frequency at this moment of time is known (Ȧ 0 İ 0 t M ), and it is near to the natural frequency. Based on the procedure described in [21], the values of the first natural frequencies are estimated experimentally. The experimental results and the numerical findings for different values of the effective piezoelectric constant d 33 * and voltage signals are compared in Fig.7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer-Aided-Engineering programs have become important tools used by engineers in the process of designing new machines and devices in recent years. A number of engineering and scientific issues, which are too complicated to be described by analytical models or difficult to test in the laboratory, have been solved using numerical methods [1,[7][8][14][15][17][18]. In addition, relatively cheap and easy access to high computing power and rapid development of computer programs implementing specific numerical methods causes that physical phenomena are modeled with incredible accuracy in relation to reality.…”
Section: Description Of the Dem Methodsmentioning
confidence: 99%
“…The natural frequency and the corresponding shape modes were investigated. Mitura et al [20] considered dynamic behaviour of the rotor with three active composite blades. The influence of the hub's angular velocity and/or piezoelectric effect on the blades' dynamics in numerical and experimental studies were determined.…”
Section: Department Of Applied Mechanics Mechanical Engineeringmentioning
confidence: 99%